Studies of cooperation protocols for cooperative wireless communication networks - Goli Prasannakumar (2016)
In this dissertation, we study communication systems employed with different cooperative relaying techniques and their performances under independent channel distributions. Several techniques have been implemented to preserve signal integrity at the receiver. One efficient way is Multiple Input Multiple Output (MIMO) technique, which uses multiple antennas and attains multiplexing by transmitting different signals through different parallel channels to increase the transmission rate. It also implements the concept of diversity where the same data is being sent through independent fading paths, and they will be combined to improve the signal-to-noise ratio (SNR) at the receiver side. Similarly, spatial diversity can also be achieved by using cooperative transmission. In this project, we study how cooperative communication achieves cooperative diversity and improves system performance without the requirement of multiple antennas. It is not always possible to incorporate multiple receiving and transmitting antennas into small mobile terminals that use battery power. This dissertation defines different cooperative relaying strategies and compares fixed relaying against adaptive relaying techniques under varying channel conditions. It also demonstrates different receiver combining techniques and different performance metrics to observe the system performance. We first focus on the performance o f the simplified relaying system with single user and then realizes with practical application of employing multiple relaying nodes to form a virtual antenna array in wireless communication systems. We simulate different cooperative techniques and plot Bit Error Rate (BER) results against the transmitted SNR values. We observe how cooperative diversity can be achieved by analyzing the performance of different relaying systems with varying the number of relays in between for the cooperation. With the help o f the simulation results, we conclude that the cooperative transmission always performs better than the direct transmission.